Reversal of stem cell‐derived hypertrophic adipocytes mediated by photobiomodulation (1064 nm). Issue 4 (8th December 2021) - McColloch, Andrew; Liu, Hanli; Cho, Michael
Abstract: Hypertrophic adipocytes have been implicated in the progression of obesity‐induced complications. These enlarged fat cells cause release of free fatty acids and inflammatory cytokines, promote hypoxia and fibrosis and limit insulin sensitivity. Photobiomodulation (PBM), or the influence of light on biological tissues, has previously been demonstrated to reduce lipid accumulation in stem cells undergoing adipogenesis. Here, we characterize the effect of PBM on an in vitro hypertrophic obesity model and its influence on reduction of lipids and restoration to normal adipocyte function. Adipose‐derived stem cells were induced to hypertrophy with the addition of palmitic acid (PA) and was confirmed with fluorescent imaging of lipid content, and functional changes such as glucose uptake. Glucose transport into the cell was diminished and the expression of glucose transporter GLUT4 was downregulated. PBM‐treated hypertrophic cells (1064 nm and 17.6 J/cm 2 every day for 7 days following addition of PA) decreased the lipid levels in hypertrophic adipocytes, restored the GLUT4 protein expression and enhanced glucose transport. Taken together, PBM is shown capable of restoring the cellular morphology and function of hypertrophic cells. This could have important clinical implication for the development of laser‐based potential therapeutic treatment of complications due to metabolic syndrome. Abstract : Adipocytic hypertrophy is a marker for dysfunctional adipose tissue that can lead to fibrosis, inflammation, oxidative stress and dysregulated metabolism. Photostimulation can be tuned and optimized to reduce fat accumulation, sequester reactive oxygen species and mitigate inflammation. Using human adipose tissue‐derived stem cells, the present study is designed to elucidate the photoregulation of adipocytic hypertrophy. It appears optimized photostimulation is capable of potentially mitigating the obesity‐associated complications (lipid in green and nucleus in blue).